Implementation of robot positioning algorithms on an urban robot (iRobot’s Packbot) - Seah, Kenneth Gee Kiat. (2010)
The Unmanned Ground Vehicle is a tool created by man to help in the task of jobs that are in hazardous nature. Those jobs include military purposes like reconnaissance of enemy troops in enemy territory, searching of land mines in a land mine field. Or exploration in nature, like multi-UGVs exploring an unknown planet surface. Many components come together to make a UGV fully operation. Part of the important aspect of an UGV is the ability to know its position with respect to its environment. The development of such ability can be done with help of cost effective simulation programs. The programs used in this project include Player/Stage project and Orca Robotics components. The localization techniques can include many different methods, the basis of this project works on the simulated odometry data from Orca Robotics. The simulated odometry data is use to localize and the position is represented on the map of the environment. By modifying an existent component from Orca Robotics the current position of the robot can be shown on the map. The other feature of this modified component is the ability to track the path taken by the robot using waypoints. The waypoints are then drawn on the map using OpenCV commands. The final tracked path can be saved on the map and be used for further references.